Technology Facilitates Physical Activity Through Gamification: A Thematic Analysis of an 8-Week Study - Kappen, Dennis L.; Mirza-Babaei, Pejman; Nacke, Lennart E. (Frontiers in Computer Science, 2020)
Gamification has enabled technology to facilitate behavior change through increasing the engagement and motivation of people in health and wellness domains. While research on physical activity (PA) and why older adults engage in PA exists, there are not many long-term studies on how gamification influences technology use and adherence to PA by older adults. We conducted a synchronous, 8-week, experimental study with older adults in the 50+ age group. Participants were randomized into three groups: Gamified technology, non-gamified technology and a control group. We conducted a weekly semi-structured interview with them focused on their PA motivations, setting up goals, accomplishments, fears or barriers, (immediate and long-term) rewards, and tracking in PA. Thematic analysis (TA) of the interview data showed these distinct variations in themes for the three groups over the 8-week period. This indicates that motivational affordances or gamification elements can be customized for older adults to suit their current health conditions and PA participation barriers. We define gamification design guidelines for PA motivation of older adults based on self-determination theory, setting up progressive goals, accomplishments to track PA quality, intangible rewards, and activity tracking.